ANALISIS PERTUMBUHAN BIBIT TANAMAN SAWI (Brassica juncea L.) PADA BERBAGAI KOMPOSISI MEDIA TUMBUH - Liastyn Dwika Putri; Nora Augustien Kusumaningrum; Pangesti Nugrahani (Plumula : Berkala Ilmiah Agroteknologi, 2018)
Various use of non-organic material is often applied in vegetable cultivation, it causes health problems for those who consume while the demand for the community will increase the need for vegetables. So it takes effort in the application of organic vegetable planting by utilizing the surrounding organic materials that are not used. Using of organic material also can increase time of harvesting, so more faster. Time of harvesting depends on growth of plants, more fertile of growing media, more faster plants can be harvested. The objectives of this study were: (1) to analyze the growth of mustard seedlings (Brassica juncea L.) (2) to get the best compositions for mustard seedlings. This research was conducted in Experimental Garden of Faculty of Agriculture of National Development University of "Veteran" East Java, Surabaya. In March to April 2017. This study was prepared in, Completely Randomized Design (RAL), with 8 treatments and 3 replications. The results showed that the addition of organic material can increase the growth rate of mustard plant seedlings in all treatments up to 4%/etmal and increase the percentage of plant growth of mustard seeds up to 90%. The result of the composition of the growing medium of P4 treatment is soil + compost + litter straw (2: 1: 1) can increase the number of leaves by 9,33 strands, plant length 38,80 cm, leaf area 60,80 cm2, dry weight 14,81 g, as well as the average total value of LTT (Plant Growth Rate) of 40% and LAB (Net Assimilation Rate) of 76% compared to using soil growth medium (P0).